Mapping Kapiti’s soils: A foundation for rangeland restoration - Tam, Kirsten; Rufino, Mariana; Gachene Charles; Slater, Annabel (International Livestock Research Institute, 2024)
Soils are the foundation of terrestrial ecosystems, holding essential water, nutrients and minerals for many critical species on the planet from plants to bacteria to fungi. Creating a baseline of knowledge for the type of soils at Kapiti at Kapiti Research Station and Wildlife Conservancy, in the semi-arid southern rangelands of Kenya, will help us test different hypotheses and tell us which factors are important for successful restoration of degraded soils. Researchers at Kapiti are studying soils to answer vital questions. How are grasslands affected by livestock and wildlife grazing? Which role does manure deposition play for microbial soil processes? What marks degraded grassland soils, and how do we restore them? And the first step is to know what type of soils are lying below the grasslands.